2001
DOI: 10.1055/s-2001-13581
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Guided Laser-Induced Interstitial Thermotherapy (SLITT) in Gliomas with Intraoperative Morphologic Monitoring in an Open MR-Unit

Abstract: Stereotactic guided laser-induced interstitial thermotherapy (SLITT) represents a minimal invasive method to produce necrosis in cerebral tumor tissue by local heating. The dose/response relationship relies on experimental studies and few clinical data performed in high field MR systems. A better understanding of the energy-dose/tissue response in human brain tumors is important to optimize this treatment modality. Twenty-four patients with gliomas were treated with SLITT, with a total of 30 laser procedures p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…A wide range of tumor sizes have been treated. Some studies 28,29,42,43,45,48 have reported short-term follow-up, demonstrating decreased perilesional edema and tumor size. Longer-term follow-up and the existence of a control population would be useful to establish the efficacy of LITT.…”
Section: Effectiveness Of This Technique With Standard Treatments (Tamentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of tumor sizes have been treated. Some studies 28,29,42,43,45,48 have reported short-term follow-up, demonstrating decreased perilesional edema and tumor size. Longer-term follow-up and the existence of a control population would be useful to establish the efficacy of LITT.…”
Section: Effectiveness Of This Technique With Standard Treatments (Tamentioning
confidence: 99%
“…Complications include wound infection, 29 neurological deficits, 7,24,27,29,34,46 vascular injuries, 27,46 and cerebral edema. 5,27 Although pooled results from these studies 5,7,24,27,29,34,46 should be interpreted with caution, given the widely varied methodologies, the overall rate of complications, which themselves range from mild to severe, was 28.6% (range 20%-50% per study). Transient or permanent neurological complications were observed in 11.1% of all patients.…”
Section: Effectiveness Of This Technique With Standard Treatments (Tamentioning
confidence: 99%
“…However, some studies have found that tissue damage caused by thermal ablation can be tissue-type dependent. 42 Moreover, tumors with similar histological grades have been shown to have variable responses to LITT, 16,[30][31][32] which makes it very challenging to standardize tumor-specific laser protocols. As explained earlier, the software links the temperature limits and the voxels in the image.…”
Section: Limitationsmentioning
confidence: 99%
“…Methods of tissue destruction include phototherapy, 2 radiofrequency lesioning, 7,40 cryoablation, 53 microwave ablation, 41,52 high-intensity focused ultrasonography, 19,32,55 and laser interstitial thermotherapy. 3,31,49 Mechanisms of tissue destruction include changes in local temperature resulting in coagulation necrosis 18,50 (radiofrequency lesioning, laser interstitial thermotherapy, and high-intensity focused ultrasonography) and cell membrane rupture 18 (cryoablation), generation of free-radicals (phototherapy), and in situ tissue fixation (microwaves). 41 Each of these techniques has selective advantages when used in the brain.…”
mentioning
confidence: 99%